The extent to which banking risk management in Libyan commercial banks contributes to improving banking financial performance (Economic studies journal, 2025)
The study aimed to know the extent to which banking risk management in Libyan commercial banks contributes to improving banking financial performance. To achieve the study objective, the descriptive analytical approach was followed in preparing the research plan. In order to collect the primary data for the study, a field survey strategy was relied upon for a sample that included banking risk management and accounting employees in Libyan commercial banks operating in the city of Sirte, using a questionnaire form. The results of the theoretical study concluded that the presence of effective risk management in banking institutions leads to achieving profitability and financial stability and enhances their ability to confront financial crises. This was confirmed by the practical aspect of this study.
Keywords: Banking risks; banking risk management; financial performance of banks; Libyan commercial banks